The Routledge Handbook of African Theology - Bongmba, Elias Kifon, 1953- (New York Routledge, 2022)
"Theology has a rich tradition across the African continent, and has taken myriad directions since Christianity first arrived on its shores. This handbook charts both historical developments and contemporary issues in the formation and application of theologies across the member countries of the African Union. Written by a panel of expert international contributors, chapters firstly cover the various methodologies needed to carry out such a survey. Various theological movements and themes are then discussed, as well as Biblical and doctrinal issues pertinent to African theology. Subjects addressed include: Orality and theology Indigenous religions and theology Patristics Pentecostalism Liberation theology Black theology Social justice Sexuality and theology environmental theology Christology Eschatology the Hebrew Bible and the New Testament The Routledge Handbook of African Theology is an authoritative and comprehensive survey of the theological landscape of Africa. As such, it will be a hugely useful volume to any scholar interested in African religious dynamics, as well as academics of Theology or Biblical Studies in an African context"--
Includes bibliographical references and indexes.
Keywords: Theology -- Africa; Theology, Doctrinal -- Africa; Postcolonial theology -- Africa; Christianity and culture -- Africa; Church and social problems -- Africa; Christianity and other religions -- African; Africa -- Religion